How Does Globalization Affect the Synchronization of Business Cycles? - Kose, Ayhan (IMF Working Papers; Working Paper ;, 2003)
This paper examines the impact of rising trade and financial integration on international business cycle comovement among a large group of industrial and developing countries. The results provide at best limited support for the conventional wisdom that globalization has increased the degree of synchronization of business cycles. The evidence that trade and financial integration enhance global spillovers of macroeconomic fluctuations is stronger for industrial countries. One striking result is that, on average, cross-country consumption correlations have not increased in the 1990s, precisely when financial integration would have been expected to result in better risk-sharing opportunities, especially for developing countries.